Integrating VOA learning English into an English listening classroom - Rahmaningtyas, Hasti; Al Mardhiyyah, Salma (citeus, 2020)
Extensive listening is crucial for language development, especially when students’ exposure to the target language is not adequate. This study presents how VOA Learning English website is integrated into an English listening classroom as a listening activity outside the class. Data were collected through questionnaires and learners' extensive listening journal weekly entries, seeking to examine students’ learning experiences and views on experiencing the website. Thirty undergraduate students participated in this study for 14 weeks. Results indicated that learners were satisfied with their learning experience as they had the chance to select materials that they found suitable and appropriate to their proficiency level and interests. Although the students did not enjoy writing the weekly journal assigned after extensive listening, they discovered that learning from VOA Learning English is convenient and useful in enriching their vocabularies and widening their knowledge of the world.